Schistosoma mansoni Coinfection Attenuates Murine Toxoplasma gondii-Induced Crohn's-Like Ileitis by Preserving the Epithelial Barrier and Downregulating the Inflammatory Response - Pêgo, Beatriz; Martinusso, Cesonia A.; Bernardazzi, Claudio; Ribeiro, Beatriz Elias; de Araujo Cunha, Aline Fernandes; de Souza Mesquita, Jacilene; Nanini, Hayandra F.; Machado, Marcelo Pelajo; Castelo-Branco, Morgana T. L.; Cavalcanti, Marta Guimarães; de Souza, Heitor S. P. (Frontiers in Immunology, 2019)
Background and aims: Mice orally infected with T. gondii develop Crohn's disease (CD)-like enteritis associated with severe mucosal damage and a systemic inflammatory response, resulting in high morbidity and mortality. Previously, helminthic infections have shown therapeutic potential in experimental colitis. However, the role of S. mansoni in T. gondii-induced CD-like enteritis has not been elucidated. Our study investigated the mechanisms underlying T. gondii-induced ileitis and the potential therapeutic effect of S. mansoni coinfection. Methods: C57BL/6 mice were infected by subcutaneous injection of cercariae of the BH strain of S. mansoni, and 7–9 weeks later, they were orally infected with cysts of the ME49 strain of T. gondii. After euthanasia, the ileum was removed for histopathological analysis; staining for goblet cells; immunohistochemistry characterizing mononuclear cells, lysozyme expression, apoptotic cells, and intracellular pathway activation; and measuring gene expression levels by real-time PCR. Cytokine concentrations were measured in the serial serum samples and culture supernatants of the ileal explants, in addition to myeloperoxidase (MPO) activity. Results:T. gondii-monoinfected mice presented dense inflammatory cell infiltrates and ulcerations in the terminal ileum, with abundant cell extrusion, apoptotic bodies, and necrosis; these effects were absent in S. mansoni-infected or coinfected animals. Coinfection preserved goblet cells and Paneth cells, remarkably depleted in T. gondii-infected mice. Densities of CD4- and CD11b-positive cells were increased in T. gondii- compared to S. mansoni-infected mice and controls. MPO was significantly increased among T. gondii-mice, while attenuated in coinfected animals. In T. gondii-infected mice, the culture supernatants of the explants showed increased concentrations of TNF-alpha, IFN-gamma, and IL-17, and the ileal tissue revealed increased expression of the mRNA transcripts for IL-1 beta, NOS2, HMOX1, MMP3, and MMP9 and activation of NF-kappa B and p38 MAPK signaling, all of which were counterregulated by S. mansoni coinfection. Conclusion:S. mansoni coinfection attenuates T. gondii-induced ileitis by preserving mucosal integrity and downregulating the local inflammatory response based on the activation of NF-kappa B and MAPK. The protective function of prior S. mansoni infection suggests the involvement of innate immune mechanisms and supports a conceptually new approach to the treatment of chronic inflammatory diseases, including CD.